Ureteral Carcinoma Complicated by Xanthogranulomatous Pyelonephritis and Ureteritis Cystica - Hama, Yukihiro; Tate, Etsuko (Department of Radiology, Medical Faculty, University of Brawijaya, 2024)
Introduction: Both xanthogranulomatous pyelonephritis (XP) and ureteritis cystica (UC) are rare diseases, and no case of coexistence with ureteral urothelial carcinoma has ever been reported. The purpose of this article is to present a case of ureteral urothelial carcinoma complicated by XP and UC and to discuss the CT and MRI findings. Case presentation: A 72-year-old woman with a history of diabetes mellitus, recurrent urinary tract infections, and bladder cancer was referred for evaluation of multiple ureteral and renal masses on the left side. No urinary tract stones were found on CT. The tumor in the lower ureter was hyperintense on diffusion-weighted image (DWI), and the tumor in the middle ureter was hypointense on DWI, showing polycystic wall thickening. DWI of the kidney showed multiple hyperintense lesions within the kidney. Pathological examination revealed tumors in the lower ureter, middle ureter, and left kidney as urothelial carcinoma, UC, and XP, respectively. Conclusion: In a patient with a history of diabetes mellitus and recurrent urinary tract infections, XP and UC should be considered in the differential diagnosis of urothelial carcinoma. Keywords: Urothelial Carcinoma, Renal Tumors, Ureteral Neoplasms, Magnetic Resonance Imaging